2019
DOI: 10.1101/827626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal Odor Reduces the Neural Response to Fearful Faces in Human Infants

Abstract: Maternal odor is known to play an important role in mother-infant-interaction in 1 many altricial species such as rodents. However, we only know very little about 2 its role in early human development. The present study therefore investigated the 3 impact of maternal odor on infant brain responses to threat signals. We recorded 4 the electroencephalographic (EEG) signal of seven-month-old infants watching 5 happy and fearful facial expressions. While infants in two control groups showed 6 the expected EEG fear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Importantly, this face-selective response increases when infants are presented with their mother's body odor compared to a baseline odor (23). This is in line with behavioral (24-28) and neural evidence (29,30) that intersensory associations mediate how infants process facial information and supports the view that the weaving of inputs from different modalities favors knowledge acquisition (for review, refer to ref. 31).…”
Section: Significancesupporting
confidence: 79%
“…Importantly, this face-selective response increases when infants are presented with their mother's body odor compared to a baseline odor (23). This is in line with behavioral (24-28) and neural evidence (29,30) that intersensory associations mediate how infants process facial information and supports the view that the weaving of inputs from different modalities favors knowledge acquisition (for review, refer to ref. 31).…”
Section: Significancesupporting
confidence: 79%
“…In humans, we similarly found that maternal BO increased infants’ sense of safety, enhanced approach, and reduced social aversion. These findings suggest that maternal presence functions as a “safety signal” for human infants, allowing them to allocate less resources to danger signals and focus on social engagement and emotional processing ( 15 ). Possibly, in humans, the species-general function of safety integrates with the effects of odor on positive arousal and visual attention to allow infants to safely explore their social environment and neutrally connect with its members.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of olfaction in humans has received less attention compared with vision and audition, anthropological studies describe the reliance on odors for group living in non-Western societies, the recognition of group odor by its members, ceremonies by which a father's smell is "transferred" to his infant, or the rubbing of body odors (BOs) by axilla sweat, suggesting that children integrate into social groups through the detection of familiar odors introduced to infants by their mother (7)(8)(9). Furthermore, studies have shown that human neonates rely on olfactory cues to recognize their mothers (10,11), and maternal chemosignals reduce pain in newborns (12), increase infant attention to face and eyes (13), shape face categorization (14), and attenuate neural response to fearful faces (15), underscoring the importance of maternal odors for orienting infants to species-critical social cues. Still, the mechanisms by which maternal BOs support maturation of the infant's social brain are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similar processes were noted in 7-month-old infants looking at happy versus fearful faces during EEG recording. While exposed to own mother's t-shirt odour, the typical brain response to the fear stimulus did not occur, whereas it clearly appeared in the control contexts (another mother's odour or no odour) [163]. The social buffering effect of maternal stimuli on HPA activation decreases in adolescents compared to royalsocietypublishing.org/journal/rstb Phil.…”
Section: Homeostatic Potency Of Maternal Odoursmentioning
confidence: 94%